Production of Compact Powder Blush on from Secang Wood (Caesalpinia sappan L.) Extract - Rety Setyawaty; Mela Dwiyanti; Dewanto Dewanto (Majalah Farmaseutik, 2020)
Secang wood (Caesalpinia sappan L.) is one of the local resources that contain natural pigments, namely brazilin. Brazilin is a pigment derived from Secang wood (Caesalpinia sappan L.) that is potentially used as a natural dye. This study aims to prove that Secang Wood (Caesalpinia sappan L.) can be applied as a dye in Compact Powder Blush On.The method for obtaining Secang wood (Caesalpinia sappan L.) extract uses the maceration extraction method with a sample of Secang wood (Caesalpinia sappan L.) of 250 gram and ethanol 96% then evaporated in a water bath with a temperature below 80 0C resulting in a yield of Secang wood (Caesalpinia sappan L.) extract of 27.87%. pH during the maceration process must be kept neutral, if it is not stable then it is added citric acid or sodium bicarbonate. The components of the Compact Powder Blush On are Talcum, Kaolin, Parrafin Liquid, Okside Zinc, Isopropyl myristate, and the addition of Secang wood extract (Caesalpinia sappan L.) with a concentration of 5%, 10%, 20%. Tests on preparations made include pH test, sticky power test, topical test, and stability test.The observations show that the Compact Powder Blush On preparation at a concentration of 5%, 10%, and 20% Secang wood extract (Caesalpinia sappan L.)  is pink, easily applied, has an average adhesion of 13.83%, produces a pink color when applying, and has a pH of 7. However, using Secang wood (Caesalpinia sappan L.) as a Blush On dye does not have color stability. Based on the results of the study it can be concluded that Secang Wood (Caesalpinia sappan L.) can be used as a natural dye Compact Powder Blush On, but additional ingredients are needed so that the color remains stable during storage at room temperature.